2016
DOI: 10.21608/jssae.2016.40465
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Total Solids Concentration on Biogas Production from Cattle Dung

Abstract: This study aimed to evaluate the effect of high total solid concentrations on biogas production from cattle dung. The evaluation process was achieved using four laboratory biogas digesters fed with fresh cow dung at three concentrations; 10 %, 15% and 20% of total solids, three different retention times of 20, 25, and 30 days and three different stirrer speeds of 80, 100, and 120 rpm. The stirring period was 15 minutes every 4 hours. The digesters have been installed inside a water bath to keep the digestion t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…James (2001) stated that the best ratio of carbon to nitrogen during the anaerobic digestion process 15-30: 1 and in particular the ratio of 20: 1 is also the range of fresh animal manure and to improve the process of anaerobic digestion inside the digester to get the optimum percentage of C:N ratio some crop residues such as plant residues and leaves are added as a carbon-rich source. El-Hadidi et al, (2016) studied the effect of high total solid concentrations on biogas production from cattle dung at three concentrations (10 %, 15% and 20%) of total solids, three different retention times of (20, 25, and 30 days) and three different stirring speeds of (80, 100, and 120 rpm) at 15 minutes every 4 hours stirring time and 40 ± 2ºC digestion. The results showed that total solids of 15% and 120 rpm stirring speeds gave the maximum average biogas production rates at different retention times.…”
Section: Introductionmentioning
confidence: 99%
“…James (2001) stated that the best ratio of carbon to nitrogen during the anaerobic digestion process 15-30: 1 and in particular the ratio of 20: 1 is also the range of fresh animal manure and to improve the process of anaerobic digestion inside the digester to get the optimum percentage of C:N ratio some crop residues such as plant residues and leaves are added as a carbon-rich source. El-Hadidi et al, (2016) studied the effect of high total solid concentrations on biogas production from cattle dung at three concentrations (10 %, 15% and 20%) of total solids, three different retention times of (20, 25, and 30 days) and three different stirring speeds of (80, 100, and 120 rpm) at 15 minutes every 4 hours stirring time and 40 ± 2ºC digestion. The results showed that total solids of 15% and 120 rpm stirring speeds gave the maximum average biogas production rates at different retention times.…”
Section: Introductionmentioning
confidence: 99%